2013
DOI: 10.4236/snl.2013.34016
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Tank Circuit for Probing Planar Lipid Bilayers

Abstract: We present first results from a hybrid coplanar waveguide microfluidic tank circuit for monitoring lipid bilayer formation and fluctuations of integrated proteins. The coplanar waveguide is a radio frequency resonator operating at ~250 MHz. Changes within the integrated microfluidic chamber, such as vesicle bursting and subsequent nanopore formation alter the reflected signal, and can be detected with nanosecond resolution. We show experimental evidence of such alterations when the microfluidic channel is fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Based on recent progress in micro-electronic andfluidic device technology [19][20][21], in conjunction with RF-circuits [22][23][24][25] dielectric spectroscopy now holds huge potential as a noninvasive and label free characterization method for single cells [26,27]. An advanced approach based on tubular CPWs (T-CPWs), was demonstrated by Bausch et al Here, the tubular CPW was employed for T cell counting, enabling enhanced detection sensitivity in the radio-frequency range at 177 MHz [28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent progress in micro-electronic andfluidic device technology [19][20][21], in conjunction with RF-circuits [22][23][24][25] dielectric spectroscopy now holds huge potential as a noninvasive and label free characterization method for single cells [26,27]. An advanced approach based on tubular CPWs (T-CPWs), was demonstrated by Bausch et al Here, the tubular CPW was employed for T cell counting, enabling enhanced detection sensitivity in the radio-frequency range at 177 MHz [28].…”
Section: Introductionmentioning
confidence: 99%
“…The aperture is fabricated in such a way that phospholipid bilayers can be spanned. The micro-strip line geometry is shown in an aerial view in figure 2(c), which is used as the basis for finite-element simulations of this particular TL [12]. The central area marked by gray boxes indicates the region where the on-chip unit is positioned.…”
Section: Initial Studies On Transmission Line Circuitsmentioning
confidence: 99%
“…Our prior experiments have demonstrated that resolving the translocation of single molecules through an α-hemolysin pore tracing the RF-response is indeed feasible [10]. The necessary next step is to place such a setup in a planar fashion with an increased sensitivity, which we have recently reported on by using a coplanar waveguide (CPW) for tracing the formation of lipid bilayers in the frequency domain [11]. In this letter we bring these first results to fruition by an enhanced CPW tank circuit design, which resolves sub-micron particle translocations with BWs greater than 30 MHz.…”
mentioning
confidence: 99%